Improving the Quality of Life of the Elderly Through Health Check-ups and Education in Budrek Village - Bandhi Prasetya Nugroho (Mitra Jurnal Pengabdian Masyarakat Multidisiplin (MJPMM), 2025)
The increase in life expectancy leads to a growing number of elderly people who require special attention, especially in terms of health and education. This community service activity aims to improve the quality of life of the elderly through routine health check-ups and education on healthy lifestyles in Budrek Grogol Village. The implementation method used a participatory approach by conducting blood pressure and blood glucose screenings, as well as interactive education on diet, physical activity, and stress management. This community service successfully improved elderly knowledge, motivated them to prevent non-communicable diseases, and provided them with access to blood pressure, glucose, uric acid, and cholesterol screening. Most participants showed elevated blood pressure levels, and some experienced increased glucose, uric acid, or cholesterol levels. The program yielded positive outcomes in terms of increased health awareness and early disease detection, and encouraged active elderly participation in maintaining their health.